Italian anarchism, transnationalism and emigration to Brazil: Contributions to theoretical debate - Romani, Carlo (Revista Crítica Histórica, 2022)
The transnational networks built by anarchists’ activists in the end of the 19th and beginning the 20th centuries, are already much known by the historiography. For Italian anarchism, due to the political persecution suffered in the 19th, transnational networks became the rule of the movement. Italian's anarchist immigration to South American cone was part of this transatlantic history. The encounter of many activists in São Paulo, Brazil, allowed the creation of several affinity groups working together, an important improve to the propaganda. In 1904, one of these efforts resulted in their aim media, “La Battaglia”, maybe the most important, certainly a very popular periodical in Brazil until 1913.